Pengembangan Manajemen Produksi dan Pemasaran Usaha Keripik Singkong Di Desa Dongos Kabupaten Jepara - Noor Azizah; Ahmat Wakit; Mohammad Faizul Musa; Annisah Immamul Latifah; Tri Ariyanti; Erix Alfiyan Hidayat; Nor Khoirotun; Andrian Dico Pratama (Universitas Semarang, 2023)
The impact of Covid-19 was felt from various sectors including MSMEs. One of them is Kripik Singkong Lancar Mandiri MSMEs in Dongos Village. The problem faced by partners is the monotony of production and management systems for selling goods. The purpose of this community service is to increase understanding and application of science and technology in society (mechanization, IT, and management) and to increase competitiveness (increasing the quality, quantity, and value of resources). The method of implementing community service includes (1) the preparation stage, the activities carried out are problem identification and data collection; (2) the implementation stage, the activities carried out are the process of training and mentoring; (3) the evaluation stage; and (4) preparation of reports stage. The results of this community service show that there is an increase in understanding and application of science and technology in society (mechanization, IT, and management) and there is an increase in competitiveness (increasing the quality, quantity, and value of resources).